Οι Νύφες του Παντελή Βούλγαρη: Το ιστορικό και κοινωνικό πλαίσιο και οι αντρικές υποκειμενικότητες - Δαμάλα Παρασκευή (Open Journal of Animation, Film and Interactive Media in Education and Culture [AFIMinEC], 2024)
The film Brides (2004) by Pantelis Voulgaris explores the phenomenon of mass migration, focusing on women from Greece, Russia, Romania, and Turkey who migrate to the United States to marry men they have selected through photographs. Their goal is social and economic advancement and to support their families. This study examines the historical and social context of the film, with a particular emphasis on the depiction of male figures. The study includes an overview of the film, presenting the main contributors, the plot, and the principal characters. It explores the historical background of the cinematic narrative and the phenomenon of migration, while analyzing male subjectivities either through their physical presence or as moral guides for the brides. The qualitative method of film narrative analysis is used to understand female migration and the role of men in the film.